A gestão de clientes insatisfeitos no segmento de TV por assinatura através de mídias sociais - Prudencio, Alexander Greif (2018)
Over the last 15 years, the relationship between industry, services and consumers has been changed a lot, mainly due to the expansion of new media social habits by consumer markets. Within the changes of this new market approach, the media social platforms became relevant elements to the business model and the customer care of the global companies. This research aimed to compare satisfaction with customer service between traditional telephone SAC channels and social media channels without human voice interaction. To achieve this objective an experiment was conducted with 60 dissatisfied customers in the Pay-TV segment. The results were statistically evaluated using the "t" test with significance range p <0.1. There was a preference for service through social media (0.008), and suggests that Facebook, as a customer care tool, had a superior result compared to the traditional SAC. As contributions, this study innovates by showing the results of managing with dissatisfied customers through a 100% digital customer care service, without voice interaction. In addition, there are few studies in Brazil on the care of unsatisfied clients carried out solely on social media, which will help reduce this gap in academic literature.